Uji Efektivitas Flavonoid Total Ekstrak Etanol Kulit Batang Nangka (Artocarpus heterophyllus Lam) Terhadap Penyembuhan Luka Sayat Pada Ayam Broiler (Gallus domesticus) - Kemalasari , Nurisma; Sumardi, Sumardi; Febriani , Yessi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2018)
Jackfruit (Artocarpus heterophyllus Lam) is a local plant found in various regions in Indonesia. This jackfruit tree is usually used as traditional medicine. This study aims to examine the ethanol extract of jackfruit bark against wound healing on broiler skin and determination of total flavonoid content using the calorimetry method. This study began with identification of plants, taking jackfruit bark, processing of jackfruit bark simplicia, making ethanol extract of jackfruit bark (Artocarpus heterophyllus Lam), measuring the total flavonoid content of ethanol extract of jackfruit bark, preparation of test animals, wound cutting on chicken skin, effectiveness test of total flavonoid ethanol extract of jackfruit bark (Artocarpus heterophyllus Lam) on wound healing in broiler chickens (Gallus domesticus), data analysis. The results showed that the administration of ethanol extract of jackfruit bark (Artocarpus heterophyllus Lam) to wound healing on the skin of broiler chickens (Gallus domesticus) had a better healing effect than negative controls. The results of applying 4 times in 24 hours provide the fastest healing effect on cuts on the skin of broiler chickens (Gallus domesticus). Based on statistical results there are 86.1% of flavonoids that affect the area of the curve and affect the healing of the area of incisions in chickens.